Glutamate/GABA co-release selectively influences postsynaptic glutamate receptors in mouse cortical neurons. (15th December 2019) - Fattorini, Giorgia; Ripoli, Cristian; Cocco, Sara; Spinelli, Matteo; Mattera, Andrea; Grassi, Claudio; Conti, Fiorenzo
Abstract: Cultured rat cortical neurons co-expressing VGLUT1 and VGAT (mixed synapses) co-release Glu and GABA. Here, mixed synapses were studied in cultured mouse cortical neurons to verify whether in mice mixed synapses co-release Glu and GABA, and to gain insight into how they may influence excitation/inhibition balance. Results showed the existence of synapses and autapses that co-release Glu and GABA in cultured mouse cortical neurons, and the ability of both neurotransmitters to evoke postsynaptic responses mediated by ionotropic receptors. We studied the short-term plasticity of glutamatergic, GABAergic, and mixed responses and we found that the kinetics of mixPSC amplitude depression was similar to that observed in EPSCs, but it was different from that of IPSCs. We found similar presynaptic release characteristics in glutamatergic and mixed synapses. Analysis of postsynaptic features, obtained by measuring AMPAR- and NMDAR-mediated currents, showed that AMPAR-mediated currents were significantly higher in pure glutamatergic than in mixed synapses, whereas NMDAR-mediated currents were not significantly different from those measured in mixed synapses. Overall, our findings demonstrate that glutamatergic and mixed synapses share similar electrophysiological properties. However, co-release of GABA and Glu influences postsynaptic ionotropic glutamatergic receptor subtypes, thus selectively influencing AMPAR-mediated currents. These findings strengthen the view that mixed neurons can play a key role in CNS development and in maintaining the excitation-inhibition balance. Highlights: Mixed synapses of mouse cortical neurons co-release Glu and GABA. Mixed and glutamatergic synapses share similar presynaptic features. Mixed synapses have fewer postsynaptic AMPA receptors than glutamatergic synapses.